Self‐prescribing of antibiotics by patients seeking care in Indian emergency departments - Janice Blanchard; Madhumathi Solaipandian; Elina Bevin John; Moin Pandith; Binu Jeo; Sherin Saji; Anil Kumar; Larissa May; Kevin Davey; Katherine Douglass; Jeffrey Smith (Journal of the American College of Emergency Physicians Open)
Abstract Study objective Antibiotic resistance is a global health threat. India has one of the highest rates of antibiotic use in the world. The objective of this study was to evaluate the prevalence of self‐prescribed antibiotic use of patients presenting with febrile and infectious disease‐related complaints to Indian emergency departments. Methods This was a prospective observational study conducted at 6 Indian emergency departments (EDs) between January 1, 2019 and December 31, 2019. Adult patients who presented with a chief complaint of febrile illness or infectious disease complaints were included. Our principal outcomes of interest were self‐prescribed use of antibiotics within the prior 6 months or for the presenting complaint. We queried respondents about source of antibiotics as well as about demographic characteristics that influenced use. Results A total of 1421 patients were enrolled. Sixty percent (n = 856) of respondents reported using antibiotics in the prior 6 months or for their current complaint. Those who reported self‐prescribing antibiotics either in the past or currently had at least some college education (P < 0.001), tended to use the pharmacy (P < 0.001) or the ED (P = 0.001) for their care when sick, and were more likely to have some comorbid conditions (P = 0.014) as compared to the group that did not self‐prescribe antibiotics. The most common reason respondents reported self‐prescribing antibiotics was because they did not want to wait to see their doctor (n = 278, 33%). Thirty‐five percent of patients who were self‐prescribed antibiotics before presentation did not receive and were not prescribed antibiotics in the ED, at discharge, or both. Conclusions Self‐prescribing of antibiotics occurs commonly in India. This use increases the risk for resistance due to inappropriate or unnecessary use. Promotion of antibiotic stewardship is needed to curtail such use.